Service Marketing Acts As Sales Booster: Exploring The Impact On Cosmetic Business (Journal of Namibian Studies : History Politics Culture, 2023)
Achieving the required sales targets is a big challenge for a seller. This study attempts to explain how service marketing approaches can be used to maximize the selling ability to create a market competitive advantage. This article is based on a detailed search of reliable databases of Science Direct and Google Scholar after a thorough examination of the available literature. There is a significant research gap because of the limited availability of research publications on the topic. The results of this study highlight the significance of service marketing as a strategic tool for academics, researchers, and policymakers. Applying the tools of service marketing boosts the sales volume of the cosmetic business. The study provides a viewpoint of the cosmetic business and how service marketing affects sales effectiveness. The study also fills the available gap in the literature.